THE EFFECTS OF RETURN ON ASSETS, CAPITAL ADEQUACY RATIO, AND FINANCING ON LIQUIDITY RISK IN SHARIA BPRS IN INDONESIA - Winda Yulias Tuti; Maizul Rahmizal; Khairil Aswan (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2022)
This study aimed to analyze the effects of return on assets (ROA), capital adequacy ratio (CAR), and financing on liquidity risk in Sharia Rural Banks/Bank Perkreditan Rakyat Syariah (Sharia BPRs) in Indonesia. The samples of the study were 40 banks registered in the Financial Services Authority (Otoritas Jasa Keuangan/OJK) selected using the purposive sampling technique. A panel regression model was used for data analysis. Data were examined using Eviews software (version 9). The research results showed that CAR had a positive and noteworthy effect on liquidity risk, while ROA and financing had a significant and negative influence on liquidity risk.